Efektivitas Penggunaan Media APE Kotak Cerdas Berhitung Terhadap Kemampuan Berhitung Anak - Rica Wijayanti; Zainudin Zainudin; Buaddin Hasan; Didik Hermanto (Mathematics Education Study Program, 2026)
The demands of the world of education are increasingly complex, this demand makes educators not only focus on presenting teaching materials but educators also have to think about how the learning process can be enjoyed by all students. One way that educators can do to make the learning process more fun and meaningful is by using Educational Game Tools (APE). Smart box counting is one form of APE media that can be used as a numeracy medium among early childhood. The purpose of this study is to prove whether or not there is an effect of the use of APE media smart box counting on children's numeracy ability. This type of research includes quasi-experimental research using a pretest-posttest design. The data analysis used in this study was a paired sample t-test. The results of the research that have been done are Sig (2 tailed) of 0.006 < 0.05, so that rejected and accepted. That is, there is an influence of the use of APE Smart Box Numeracy media on Children's Numeracy Ability.